PENGARUH RASIO PASAR, KURS RUPIAH, INFLASI, DAN HARGA BATUBARA DUNIA TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR ENERGI DI BEI TAHUN 2019-2024 - Dinar Nursyahbani; Sri Isfantin Puji Lestari; Dian Noor Citra Perdana (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of market ratios (Earning Per Share/EPS), the rupiah exchange rate, inflation, and world coal prices (Newcastle Coal Future) on the stock prices of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 period. The study employs a quantitative approach using multiple linear regression analysis (OLS method). The sample consists of 40 energy sector companies selected through purposive sampling, resulting in 240 observation units. The theoretical foundations are the Signaling Theory (Spence, 1973; Ross, 1977) and the Efficient Market Hypothesis (Fama, 1970). The results show that partially, only EPS has a positive and significant effect on stock prices (t=15.952; Sig.<0.001; Beta=0.731), making it the most dominant variable in the model. The rupiah exchange rate has a positive but insignificant effect (Sig.=0.311), inflation has a negative but insignificant effect (Sig.=0.812), and world coal prices have no significant direct effect (Sig.=0.673). Simultaneously, all independent variables significantly influence stock prices (F=64.783; Sig.<0.001) with a model explanatory power of 51.6% (Adjusted R²=0.516). These findings imply that EPS is the primary market signal in valuing energy sector stocks, while macroeconomic variables function more as leading indicators to anticipate future EPS movements. Keywords: Earning Per Share (EPS), Rupiah Exchange Rate, Inflation, Newcastle Coal Price, Energy Sector